Impact of thermal treatment and hydrolysis by Alcalase and Cynara cardunculus enzymes on the functional and nutritional value of Okara - Voss, Glenise B. (2020)
Enzymatic hydrolysis of dried okara (autoclaved and non-autoclaved) with Alcalase (AL) and Cynara cardunculus extract (CY) was studied, assessing the impact of heat treatment and hydrolysis on potential antioxidant and antihypertensive activities of final hydrolysates. This study showed that the thermal treatment (sterilization at 121 °C, 1 atm and 15 min) facilitated the enzymatic access to substrate and increased the degree of hydrolysis (DH), especially for AL (37.9%) when compared to CY (3.6%). The antioxidant activity of dried Okara (either autoclaved or not) when hydrolysed with AL was higher (4.2 mg Trolox/mL) than that observed for CY. Additionally, the potential ACE-inhibitory activity was high for samples hydrolysed with both enzymes, however the highest ACE inhibition was also found for AL (IC50 = 9.97 µg/mL). This study allowed the identification of new peptide sequences in dried okara hydrolysed with both enzymes, and some sequences that can explain their bioactivities. The results indicate that dried okara hydrolysates can either be used as functional ingredient or as food supplement for blood pressure lowering or antioxidant applications in the future.